Frosty the snowman - Rankin, Arthur, Jr.; Bass, Jules; Muller, Romeo; Goldstick, Oliver; Lewis, Jim.; Casemiro, Eryk.; Melendez, Bill.; Brown, Evert; Durante, Jimmy; De Wolfe, Billy, 1907-1974.; Vernon, Jackie; Winters, Jonathan; et al. (New York : Sony Wonder : Classic Media, 2004)
Frosty the snowman: When Frosty comes to life, he must weather a storm of adventures and the plans of an evil magician before he can find safety and happiness at the North Pole. Frosty returns: When a power-hungry tycoon invents a product that will eliminate snow, Holly must convince the people of Beansboro to save the snow and her friend Frosty.
Animated.
Frosty the snowman: camera, Nick Vasu ; animation, Mushi Studio ; character design, Paul Coker, Jr. ; continuity design, Don Duga ; musical director, Maury Laws. Frosty returns: animation, Sam Jaimes ... [et al.] ; painters, Sybil Cuzzort ... [et al.] ; editing, Chuch McCann, Warren Taylor ; music, Mark Mothersbaugh.
Frosty the snowman: told and sung by Jimmy Durante ; voices of Billy DeWolfe (Magician), Jackie Vernon (Frosty), Paul Frees, June Foray.
Frosty returns: voices of Jonathan Winters (Narrator), Jan Hooks, Andrea Martin, Brian Doyle-Murray, Elisabeth Moss, Michael Patrick Carter, John Goodman (Frosty).
Frosty the snowman originally broadcast as television program 1969. Frosty returns originally broadcast 1992.
DVD, Region 1, Dolby digital.
Keywords: Snowmen -- Drama; Christmas films; Television programs for children; Films for the hearing impaired; Animated television programs